Autofluorescence of the crystalline lens in early and late onset diabetes. - Sparrow, J; Bron, A; Brown, N; Neil, H (BMJ Publishing Group, 1992)
Blue/green autofluorescence (excitation around 420 to 430 nm, emission around 520 nm) of the crystalline lens has been studied by an in vivo photographic method in two populations of diabetics and controls. The populations consisted of a geographically based survivor group of 161 mixed early and late onset diabetics (and 133 non-diabetic controls) and a second group of 104 early onset insulin dependent diabetics (and 138 non-diabetic controls), the latter all with non-cataractous lenses. Powerful associations (p less than 10(-6) were found between the presence of diabetes and increased lenticular autofluorescence in both populations. Among the mixed diabetics diabetic type was a significant factor after accounting for the effects of age and diabetic duration. In the early onset group (clear lenses) a powerful association existed between autofluorescence and diabetic duration (p = 0.000011) after allowing for the effect of age, while in a subgroup of late onset diabetics with clear lenses this effect was modest (p = 0.015). In the early onset diabetic group diabetic retinopathy (p = 0.0064) was associated with increased lenticular autofluorescence after allowing for the effects of age and diabetic duration. In addition a powerful interaction between diabetic duration and the presence of diabetic retinopathy (p less than 10(-6) was found in this subgroup. Among the geographically based population of diabetics, increased nuclear brunescence was powerfully associated (p less than 10(-6) with increased autofluorescence after allowing for the effects of age, diabetic duration, and type of diabetes. This association was not found in the non-diabetic population. Non-enzymatic glycosylation of lens proteins should be considered as a possible mechanism of production of the fluorogen with emission around 520 nm.